Perbandingan Contrast Water Therapy dan Kompres Dingin terhadap Derajat Phlebitis Pasien yang Di Infus - Edi Supriadi (Syntax Idea, 2021)
The purpose of this study was to find out the difference in effectiveness between CWT and cold compresses against phlebitis degrees in patients who were infused in hospitals. Dustira Cimahi. Experimental quasi-research method with two groups pretest and posttest design approach, with a sample number of 44 patients using purposive sampling, intervention group using CWT and control group using cold compress. The results showed a difference in phlebitis degree score before and after cold compresses (pretest 2.32 and posttest 1.68) which showed a decrease in phlebitis degree score. In the group that used CWT, there was a difference in phlebitis degree score (pretest 2.41 and posttest 1.32), with p= 0.000, this showed a decrease in phlebitis degree score and the significance of the difference in average phlebitis degree score before and after intervention. The mean value of the intervention and control group is negative with the difference in phlebitis degrees between the intervention group and the control group (p=0.026). A decrease in the degree of flebititis in the CWT group occurred in the third treatment, while in the cold compress group occurred in the fifth treatment. The results of both interventions were effective in lowering phlebitis, but CWT was more effective when compared to cold compresses. It is recommended that nurses can be used as one of the evidance-based nursing that serves as the rational basis for the implementation of Contrast Water Therapy as an independent nursing intervention to reduce the degree of phlebitis quickly without causing additional accumulation of edema. Based on the results of research and discussion, the conclusions in this study are both interventions both CWT and cold compresses are equally effective in lowering the degree of phlebitis, but CWT interventions are more effective and faster to lower the degree of phlebitis in patients who are infused when compared to cold compresses.